On the trail of a trail, the trace of a trace. Kazimierz Przerwa-Tetmajer’s Cień Chopina and its compositional interpretations - Gmys, Marcin (Interdisciplinary Studies in Musicology, 2018)
At the beginning of this article, the author points out how quickly the image of Chopin as an artist who wrestled all his life with a mortal sickness (Chopin as a “singer of Weltschmerz”) took shape - an image which was subsequently taken up by European art of the fin de siecle. Attention then turns to the poem Cień Chopina [Chopin’s shadow], by the poet Kazimierz Przerwa-Tetmajer, highly fashionable during the Young Poland period, which can be ascribed to the “Weltschmerz current”. In contrast to earlier interpreters of this lyric, the author does not identify the lyrical subject of Tetmajer’s poem with the shadow (that is, the soul) of the Polish composer, but - referring to the observations of Barbara Sienkiewicz, who applied the Heideggerian formula of the “trace of a trace” to her exegesis of Tetmajer’s works - maintains that its hero is the shadow of Chopin’s shadow (or the shadow of his soul). Going on to analyse four song settings of this poem composed during the period 1900-1926 by Władysław Żeleński, Stanisław Lipski, Juliusz Wertheim and Ryta Gnus, and also the composition Cień Chopina by Witold Friemann (1913-46), scored for piano, baritone and orchestra, the author arrives at the conclusion that four composers - Żeleński, Wertheim, Gnus and Friemann - interpreted Tetmajer’s lyric in a way that is not entirely in keeping with the poet’s intentions. These composers, employing stereotypical Chopin formulas (a quasi-folk drone or chords imitating bells) or allusions to specific Chopin works, treated the lyrical subject of Tetmajer’s poem as identical to Chopin’s soul. Only Stanisław Lipski, who in his song forged a “pastoral scene”, referring to some extent to the most important features of the pastoral idiom elaborated by Beethoven on the pages of his Sixth Symphony, interpreted the figure of the lyrical subject of Tetmajer’s poem, listening to voices from the past, as a “double epiphenomenon” - a shadow of Chopin’s shadow.